Clinical features and prognostic factors of cryptococcal infections in HIV-infected patients: a 10-year study from an infectious disease specialist hospital - Dai, Fang-Fang; Lou, Jin-Li; Yu, Yan-Hua; Chen, Ming; Lu, Xin-Xin (Frontiers in Cellular and Infection Microbiology, 2024)
Background Cryptococcosis is an invasive infection that commonly affects immunosuppressed individuals, especially patients with HIV infection. Cryptococcal infection in HIV-infected patients should be considered a major health concern because it is associated with high morbidity and mortality rates. In this study, we aimed to evaluate the clinical characteristics and prognostic factors of cryptococcal infections in human immunodeficiency virus (HIV)-infected patients to facilitate effective clinical management and improve patient outcomes. Methods We reviewed and analyzed the clinical data and relevant laboratory test results of HIV-infected patients with positive cryptococcal cultures and reserved strains between 2013 and 2023 from Beijing Youan Hospital affiliated to Capital Medical University. The clinical characteristics and laboratory test results of the patients were compared, and the correlation between parameters and the prognoses of the patients at different observation timepoints (3, 6, 9, and 12 months) was analyzed. Results A total of 76 patients (70 males and six females; median age, 37 years) were included in this study. The results indicated that the later the initiation of antiretroviral therapy (ART) after the diagnosis of HIV infection (> 6 months), the higher the probability of death. Analysis of the correlation between the time of ART initiation and the timing of treatment for cryptococcal infections showed that the time of ART initiation was strongly related to survival at different timepoints. Initiation of ART time within 0-4 weeks, 4-6 weeks and more than 6weeks of starting treatment for Cryptococcus infection was associated with a lower mortality rate at 12-month, the 3-month, 6- and 9-month follow-up timepoint separately. Conclusions Although cryptococcal infection in HIV-infected patients continues to be a challenging and intricate issue, ART is a key factor that affects its prognosis. The later ART is started, the worse the prognosis of the infection. The time of ART initiation and the timing of treatment for cryptococcal infections should be further refined and balanced based on different clinical courses. Thus, clinicians should pay closer attention to cryptococcal infections in patients with HIV infection and initiate ART based on the patient’s clinical condition.